Safe and high-rate supercapacitors based on an "acetonitrile/water in salt" hybrid electrolyte. Issue 11 (11th July 2018) - Dou, Qingyun; Lei, Shulai; Wang, Da-Wei; Zhang, Qingnuan; Xiao, Dewei; Guo, Hongwei; Wang, Aiping; Yang, Hui; Li, Yongle; Shi, Siqi; Yan, Xingbin
Abstract : An "acetonitrile/water in salt" electrolyte with non-flammability, high conductivity, a high stability window and a wide applicable temperature range enables high-performance supercapacitors. Abstract : The properties of the electrolyte are the dominant factors for the overall performance and safety of electrical energy storage devices. Highly concentrated "water in salt" (WIS) electrolytes are inherently non-flammable, moisture-tolerant, and exhibit wide electrochemical stability windows, making them promising electrolytes for high-performance energy storage devices. However, WIS electrolytes possess intrinsically low conductivity and high viscosity, which usually impair the high-rate performance of many energy storage devices, especially supercapacitors (SCs). Additionally, the inevitable salt precipitation at low temperature for WIS electrolytes narrows down their applicable temperature range. Here, we introduce acetonitrile as a co-solvent to a typical "water in salt" electrolyte to formulate an "acetonitrile/water in salt" (AWIS) hybrid electrolyte that provides significantly improved conductivity, reduced viscosity and an expanded applicable temperature range while maintaining the aforementioned important physicochemical properties of WIS electrolytes. Using the AWIS electrolyte for a model SC remarkably enhances the high-rate performance, accompanied by a 2.4 times capacitance increase at 10 A g −1 with respect to the original WIS electrolyte. This AWIS electrolyte also enables a stable long-term cycling capability of the model SC for over 14 000 cycles at a high operation voltage of 2.2 V.